Polymers Synthesis and Characterization (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Polymer science represents a domain of great interest due to the possible applications of polymers in areas that range from the most common to those that are high-tech. To achieve this, synthesis and characterization techniques, as well as the correlation of the chemical structure and morphology with their properties, is critical. From the perspective of synthesis, there are two strategies for obtaining polymers: step-growth (polyaddition, polycondensation, and reversible-deactivation radical polymerization) and chain polymerization (radical polymerization, coordinative polymerization, and cationic and anionic polymerization).The advancement of polymer applications continues to lead to the expansion of the synthesis and characterization techniques that can be facilitated by novel, smart, multifunctional polymers. There is a correlation between structure, composition, morphology, and properties of applications that leads to substantial benefits for specific applications.This Special Issue will establish a collection of articles and reviews that follow the latest developments in polymer synthesis, their characterization techniques, and the correlation between structure and properties.